Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1371/journal.pone.0074737
|View full text |Cite|
|
Sign up to set email alerts
|

Cryptococcus gattii in the United States: Genotypic Diversity of Human and Veterinary Isolates

Abstract: Background Cryptococcus gattii infections are being reported in the United States (US) with increasing frequency. Initially, US reports were primarily associated with an ongoing C . gattii outbreak in the Pacific Northwest (PNW) states of Washington and Oregon, starting in 2004. However, reports of C . gattii infections in patients from other US states have been increasing since 2009. Whether this is due to increasing frequency of disease, greater recognition within the clinical community, or both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
90
4
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 80 publications
(102 citation statements)
references
References 63 publications
(60 reference statements)
2
90
4
5
Order By: Relevance
“…Other sequence types identified in our study have been also reported before from Asia (ST5 and ST32), Africa (ST5, ST23, ST39, and ST43), and the United States (ST32) (40)(41)(42)(43)(44)(45). Molecular type VNI, VNII, VGI, and VGII isolates from dogs and cats in this study had sequence types that were identical or closely related to those of the reference VGI and VGII strains, respectively, supporting the more clonal relationship of these populations as described previously (15,16).…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Other sequence types identified in our study have been also reported before from Asia (ST5 and ST32), Africa (ST5, ST23, ST39, and ST43), and the United States (ST32) (40)(41)(42)(43)(44)(45). Molecular type VNI, VNII, VGI, and VGII isolates from dogs and cats in this study had sequence types that were identical or closely related to those of the reference VGI and VGII strains, respectively, supporting the more clonal relationship of these populations as described previously (15,16).…”
Section: Discussionsupporting
confidence: 90%
“…However, infections with C. gattii molecular type VGIII were recently identified in human patients with HIV/AIDS from southern California (16). A lower number of molecular type VGIII isolates have been isolated from humans in other states, including those in the Pacific Northwest, the south, Michigan, and Alaska (15), although the travel history of many of the infected individuals in these states was unknown. Analysis of VGIII isolates infecting humans in the United States has shown a genetically diverse population of isolates that includes both mating types ␣ and a and that can be separated into VGIIIa and VGIIIb subclusters (15,16).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations